Virtualization with VMware ESX Server - Muller, Al. (Rockland, MA : Syngress, 2005)
This book will detail the default and custom installation of VMwares ESx server as well as basic and advanced virtual machine configurations. It will also discuss the requirements for a server virtualization and consolidation project and the cost savings surrounding such an effort. Furthermore, the book will provide a thorough understanding of the benefits of a virtual infrastructure and a comprehensive examination of how VMware eases administration and lowers overall IT costs. Lastly, the book delivers a thorough understanding of the virtual evolution which is underway in many IT organizations and how the reader will benefit from shifting from the physical to a virtual * A detailed resource on the default and custom installation of VMware's ESx server * Covers all the requirements for a server virtualization and consolidation project and the cost savings surrounding such an effort * Delivers a thorough understanding of the virtual evolution occuring in the IT industry.
Chapter 1 Introduction to VMware Terms and Concepts ; Chapter 2 Loading VMware ESX Server 2.1.2 ; Chapter 3 Configuring a Virtual Machine and Gold Builds ; Chapter 4 Advanced Configurations including Clustering ; Chapter 5 Physical to Virtual Migrations ; Chapter 6 Server Consolidation ; Chapter 7 Cool Tools for a Virtual Infrastructure ; Chapter 8 Administering a Virtual Infrastructure ; Chapter 9 Gotchas/Common Problems and their Solutions ; Chapter 10 VMware under the Covers ; Chapter 11 Virtual Evolution and the Road Ahead ; Chapter 12 Backups made simpleScripts and all ; Chapter 13 A Peak at the FutureIts Totally Cool ; Chapter 14 Microsofts Virtual Server 2005. Connectix on roids.
Includes bibliographical references (p. 450) and index.
Keywords: VMware; Operating systems (Computers).; Virtual computer systems; Electronic books